Fibroblast Growth Factor 21 and Metabolic Dysfunction in Women with a Prior Glucose-Intolerant Pregnancy - Durnwald, Celeste; Mele, Lisa; Landon, Mark B.; Varner, Michael W.; Casey, Brian M.; Reddy, Uma M.; Wapner, Ronald J.; Rouse, Dwight J.; Tita, Alan T. N.; Thorp, John M., Jr.; Chien, Edward K.; Saade, George R.; Peaceman, Alan M.; Blackwell, Sean C.; for the Eunice Kennedy Shriver National Institute of Child Health Human Development (NICHD) Maternal Fetal Medicine Units (MFMU) Network (American Journal of Perinatology, 2020)
Objective We sought to determine if there is an association between fibroblast growth factor 21 (FGF21) levels and a history of gestational diabetes mellitus (GDM) in women with and without metabolic dysfunction, defined as a diagnosis of metabolic syndrome or type 2 diabetes (T2DM), 5 to 10 years following participation in a multiple cohort GDM study.Study Design At 5 to 10 years after index pregnancy, women underwent a follow-up visit and were categorized as having no metabolic syndrome, metabolic syndrome, or T2DM. FGF21 levels were compared between women who did and did not have a history of GDM using multivariable linear regression.Results Among 1,889 women, 950 underwent follow-up and 796 had plasma samples analyzed (413 GDM and 383 non-GDM). Total 30.7% of women had been diagnosed with T2DM or metabolic syndrome. Overall, there was no difference in median FGF21 levels in pg/mL between the prior GDM and non-GDM groups (p = 0.12), and the lack of association was observed across all three metabolic categories at follow-up (p for interaction = 0.70).Conclusion There was no association between FGF21 levels and prior history of mild GDM in women with and without metabolic dysfunction 5 to 10 years after the index pregnancy (ClinicalTrials.gov number, NCT00069576, original trial).
Keywords: fibroblast growth factor; gestational diabetes; glucose intolerance; metabolic syndrome